2018
DOI: 10.1039/c7cp07061f
|View full text |Cite
|
Sign up to set email alerts
|

Two dimensional crowding effects on protein folding at interfaces observed by chiral vibrational sum frequency generation spectroscopy

Abstract: The crowding effect is prevalent in cellular environments due to high concentrations of biomacromolecules. It can alter the structures and dynamics of proteins and thus impact protein functions. The crowding effect is important not only in 3-dimensional cytoplasm but also for a 2-dimensional (2D) cell surface due to the presence of membrane proteins and glycosylation of membrane proteins and phospholipids. These proteins and phospholipids - with limited translational degrees of freedom along the surface normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 58 publications
1
23
0
Order By: Relevance
“…Another possible explanation can be given by considering molecular crowding (Liu et al, 2018 ) and induced changes in lipid composition and their asymmetry (Bigay and Antonny, 2012 ; McMahon and Boucrot, 2015 ) at the contact perimeter, which may even lead to local conformational switches (Aisenbrey et al, 2008 ) and nano-domain clustering, as observed for glycolipid GM3 and PIP2 in molecular simulations of complex lipid bilayers (Koldsø et al, 2014 ). The large headgroups in PIP3 confers an inverted conical shape to the lipids, thereby favoring the bending of the membrane into a positive curvature (Di Paolo and De Camilli, 2006 ; McMahon and Boucrot, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another possible explanation can be given by considering molecular crowding (Liu et al, 2018 ) and induced changes in lipid composition and their asymmetry (Bigay and Antonny, 2012 ; McMahon and Boucrot, 2015 ) at the contact perimeter, which may even lead to local conformational switches (Aisenbrey et al, 2008 ) and nano-domain clustering, as observed for glycolipid GM3 and PIP2 in molecular simulations of complex lipid bilayers (Koldsø et al, 2014 ). The large headgroups in PIP3 confers an inverted conical shape to the lipids, thereby favoring the bending of the membrane into a positive curvature (Di Paolo and De Camilli, 2006 ; McMahon and Boucrot, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The resulting partially folded conformation of the synuclein was resistant to aggregation, suggesting that the abundance of membrane‐bound proteins in living cells likely affects the conformational equilibrium of IDPs [151]. Somewhat differently to IDPs, folding of a small, 31 amino acid long zinc finger protein covalently anchored to a lipid monolayer at a high density could not be accomplished, likely due to steric repulsion between otherwise structured domains [152]. Under these crowded conditions and reduced degrees of freedom, the protein acquired partial α‐helical fold.…”
Section: Membrane‐associated Protein Aggregation Under Crowded Conditmentioning
confidence: 99%
“…This is most likely caused by the presence of the other ion channels whose interfacial ion populations all have to compete for the same space. This crowding effect could be important in regulatory structures where the ion channel density is high …”
mentioning
confidence: 99%